Characterization of Metabolites of Leonurine (SCM-198) in Rats after Oral Administration by Liquid Chromatography/Tandem Mass Spectrometry and NMR Spectrometry - Qing Zhu; Jinlian Zhang; Ping Yang; Bo Tan; Xinhua Liu; Yuanting Zheng; Weimin Cai; Yizhun Zhu (The Scientific World Journal)
Leonurine, a major bioactive component from Herba Leonuri, shows therapeutic potential for cardiovascular disease and stroke prevention in some preclinical experiments. The aim of this study is to characterize metabolites of leonurine in rats using high performance liquid chromatography coupled with tandem mass spectrometry (HPLC/MS/MS). The chromatographic separation was performed on an Agilent ZORBAX SB-C18 column using a gradient elution with acetonitrile/ammonium acetate buffer (10 mM, pH 4.0) solvent system. An information dependent acquisition (IDA) method was developed for screening and identifying metabolites of leonurine under positive ion mode. Compared with control, the interesting compound in the extracted ion chromatogram (XIC) of the in vivo samples was chosen and further identified by analyzing their retention times, changes in observed mass (Δm/z), and spectral patterns of product ion utilizing advanced software tool. For the first time, a total of three metabolites were identified, including two phase II metabolites generated by glucuronidation (M1) and sulfation (M2) and one phase I metabolite formed by O-demethylation (M3). Finally, the lead metabolite M1 was isolated from urine and its structure was characterized as leonurine-10-O-β-D-glucuronide by NMR spectroscopy (1H, 13C, HMBC, and HSQC).